Fishes of the Western North Atlantic. Neoscopelidae and Myctophidae and Atlantic mesopelagic zoogeography /: Neoscopelidae and Myctophidae and Atlantic mesopelagic zoogeography. Order Iniomi (Myctophiformes) : Part 7, ([2018]) - Nafpaktitis, Basil G, 1929-; Backus, Richard H; Craddock, James E; Haedrich, R. L, 1938-2017; Robison, Bruce H; Karnella, Charles
No abstract available